2014
DOI: 10.1371/journal.pone.0106007
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Prognostic Model Predicts Esophageal Squamous Cell Carcinoma Prognosis

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) has the highest mortality rates in China. The 5-year survival rate of ESCC remains dismal despite improvements in treatments such as surgical resection and adjuvant chemoradiation, and current clinical staging approaches are limited in their ability to effectively stratify patients for treatment options. The aim of the present study, therefore, was to develop an immunohistochemistry-based prognostic model to improve clinical risk assessment for patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…Knockdown of SP1 inhibited growth, migration and tumorigenicity of MPM cells, strongly suggesting that SP1 functions as an oncogene in MPM. Whereas SP1 over-expression has been associated with decreased survival of patients with lung and esophageal cancers {Sun, 2014 2914 /id;Cao, 2014 2915 /id}, our micro-array experiments did not reveal an association between SP1 mRNA expression and survival in MPM patients, possibly due to the limited number of samples analyzed, as well as potential discrepancies between mRNA and protein levels detected in MPM specimens using various techniques. Additional experiments demonstrated that MM markedly diminished growth of MPM cells in-vitro and in-vivo via induction of DNA damage, cell cycle arrest and senescence with subsequent apoptosis.…”
Section: Discussioncontrasting
confidence: 68%
“…Knockdown of SP1 inhibited growth, migration and tumorigenicity of MPM cells, strongly suggesting that SP1 functions as an oncogene in MPM. Whereas SP1 over-expression has been associated with decreased survival of patients with lung and esophageal cancers {Sun, 2014 2914 /id;Cao, 2014 2915 /id}, our micro-array experiments did not reveal an association between SP1 mRNA expression and survival in MPM patients, possibly due to the limited number of samples analyzed, as well as potential discrepancies between mRNA and protein levels detected in MPM specimens using various techniques. Additional experiments demonstrated that MM markedly diminished growth of MPM cells in-vitro and in-vivo via induction of DNA damage, cell cycle arrest and senescence with subsequent apoptosis.…”
Section: Discussioncontrasting
confidence: 68%
“…Fascin-1, a member of cytoskeleton proteins, induces the formation of filopodia, lamellipodia, and microspikes of the cell membrane after cross-linking with F-actin, by facilitating the movement, metastasis, and invasion of tumor cells [45]. Multiple investigations have speculated that overexpression of Fascin-1 was associated with a variety of human malignancies, such as pancreatic [46], esophageal [47], breast [48] and colorectal cancers [49]. In line with these notions, our study provided further evidence to satisfy an unmet clinical need.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic model for EC has been continuously updated [25][26][27]. In this study, we identi ed 247 up-regulated and 56 down-regulated IRGs in EC and screened out survival-related IRGs.…”
Section: Discussionmentioning
confidence: 99%